Effect of starch liberation method and initial pH of sweet mashes on higher alcohols content in distillates obtained from different starchy raw materials. (October 2018) - Pielech-Przybylska, Katarzyna; Balcerek, Maria; Dziekońska-Kubczak, Urszula; Patelski, Piotr; Różański, Mateusz
Graphical abstract: Highlights: Content of higher alcohols is closely related to the type of raw material used. Trace-amount alcohols are mainly associated with method of starch liberation. Initial pH of sweet mashes has an effect on the content of 1- and 2-propanol. Abstract: The qualitative and quantitative profile of volatile compounds in agricultural distillate depends on numerous factors. Many such compounds, including higher alcohols, occur naturally, due to the metabolism of yeast during ethanol fermentation. Some are difficult to remove in the rectification process. For these reasons, it is desirable to reduce the synthesis of volatile compounds, among others higher alcohols, during the fermentation process. The results of the presented study showed that the raw materials, the method of starch liberation, and the initial pH of the sweet mashes affected the concentrations of higher alcohols in the distillates. Higher concentrations of 1-butanol, 1-propanol, and 2-propanol were found in distillates obtained from mashes prepared by the thermal-pressure method, while the remaining compounds occurred at higher concentrations in distillates obtained using the pressureless starch liberation method. The type of raw materials used had an influence on the concentration of the majority of higher alcohols. The content of 2-propanol, 2-methyl-1-propanol, 1-propanol, 1-butanol, 3-methyl-1-butanol, and 2-phenylethanol was lower in distillates obtained from mashes with an initial pH of 4, in comparison with those obtained from mashes with the pH set at 5.5.